The Role of Social Media in Family Communication: Opportunities and Challenges in the Digital Era - Ambarsari, Dewi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
In today's digital age, social media has become a fundamental part of everyday life, especially in the context of interactions between family members. As a platform that facilitates communication despite physical distance, social media serves not only as a communication tool but also as a medium for strengthening emotional bonds among family members. This study aims to understand the role of social media in family communication in the digital age, as well as to identify its benefits, challenges, and impact on relationships between family members. Using a qualitative research approach through in-depth interviews with informants in South Jakarta, this study reveals that social media, particularly WhatsApp, serves as an effective tool for maintaining flexible and rapid communication amid busy schedules and physical distance. Additionally, social media can strengthen emotional bonds, facilitate self-expression, and enhance openness and support within families. However, the use of social media also presents challenges, such as the potential for reduced direct interaction, the risk of misinterpreting messages, and a decrease in face-to-face gathering time. The research findings highlight the importance of using social media wisely and in moderation to maximize its positive potential while minimizing its negative impacts. This study is expected to provide insights for families in optimizing the benefits of social media as a communication tool that can strengthen family bonds in the digital age while maintaining direct interpersonal relationships.